Anaemia and iron deficiency in athletes. Practical recommendations for treatment - Chatard, J. C.; Mujika, I.; Guy, C.; Lacour, J. R. (Sports Medicine, 1999)
Trained athletes frequently experience low levels of blood haemoglobin (13 to 14 g/100ml in men and 12 g/100ml in women) plus low haematocrit and low ferritin levels. These parameters define the concept of 'sports anaemia'. Low iron levels may be due to mechanical haemolysis, intestinal bleeding, haematuria, sweating, low iron intake or poor intestinal absorption. The resulting decrease in blood gas transport and muscle enzyme activity impairs performance. The concept of sports anaemia can be criticised. Simply measuring the blood levels does not take into account the haemodilution that occurs in athletes because of training. The lack of these measurements makes it difficult to diagnose anaemia or evaluate any treatment. Anaemia is treated by preventing decreased iron stores through a balanced food intake or iron supplements. Self-medications must be discouraged because of intolerance, risk of overdose and many other drug interactions. (Source: Sports Med 1999 Apr;27(4):229-40 )